“Can A Ballerina Eat Ice Cream?”: A Mixed-Method Study on Eating Attitudes and Body Image in Female Ballet Dancers - Santo André, Heloisa C.; Pinto, Ana Jessica; Mazzolani, Bruna Caruso; Smaira, Fabiana Infante; Ulian, Mariana Dimitrov; Gualano, Bruno; Benatti, Fabiana Braga (Frontiers in Nutrition, 2022)
Aim: We aimed to explore how a group of classical ballet dancers perceived their eating attitudes and their bodies, with special attention to the potential presence of eating disorders symptoms and body image (dis)satisfaction. Methods: A cross-sectional, mixed-method study was conducted on fourteen trained classical ballet dancers (18-30 years old). Their experiences, perceptions and feelings regarding eating attitudes and body image in relation to classical ballet was acquired through qualitative focus groups. Presence of eating disorders (EDs) symptoms and perception and (dis)satisfaction with body image was analyzed quantitatively through self-report questionnaires. Results: Participants reported concerning eating attitudes during the focus groups, such as the regular practice of several restrictive popular diets, constant restriction of foods considered “heavy” or “fatty”, meal skipping and ignoring signs of hunger, presence of overating episodes due to stress and anxiety, feeling guilty about breaking their usual diet, classifying foods as “good” and “bad” or “lean” and “fat”, and excluding some of those foods from their usual diets. These reports were partially reflected in the questionnaires, with 50% of the ballerinas showing bulimic symptoms indicative of an unusual eating pattern (only two of them with a significant risk index), 7.1% showing symptoms of moderate binge eating and 14.3% symptoms of EDs in general. Additionally, when considering their bodies in the context of everyday life, participants were satisfied; however, in the "classical ballet" context, they reported feeling dissatisfied with their shape. These findings were in line with results from the Stunkard's Scale which revealed that 50% of the sample was dissatisfied with their current body shape and 57.1% indicated that their desired body shape was a leaner figure than one they considered healthy. Conclusions: The constant practice of restrictive diets and other weight loss strategies to achieve a leaner body were associated with symptoms of EDs and body dissatisfaction in this sample. Importantly, the questionnaires seemed to underestimate the presence of a disordered eating pattern reported by the participants during focus groups. This data could help to inform psychological and nutritional strategies aimed at improving performance, physical and psychological well-being, and quality of life of ballet dancers.